Digital Literacy of Rural Farmers in Western Hills of Nepal: A Case of Rishing Rural Municipality - Bohara, Abichar; Gurung, Yogendra B. (Asian Journal of Population Sciences, 2025)
This study aimed to measure the digital literacy of rural farmers in the western hills of Nepal. Using a five-point Likert scale, 27 questions were initially designed based on six proposed factors: device and software operations, information and data literacy, communication and collaboration, digital content creation, safety, and problem-solving. Data collected from 383 participants revealed that 296 owned smartphones; thus, digital literacy was assessed for these individuals. Initial Exploratory Factor Analysis (EFA) suggested a more robust model with four factors and 15 indicators, subsequently validated through Confirmatory Factor Analysis (CFA). Descriptive statistics and mean scores were calculated, and digital literacy levels were analyzed across demographic variables such as gender, age, and education. Results indicated that approximately 53% of rural farmers demonstrated high digital literacy, with an overall mean score of 47.97 (SD = 15.49). The findings emphasized the need for targeted interventions to equip rural farmers with essential digital skills for modern agricultural practices and offer valuable insights for policymakers and institutions to enhance digital literacy in rural communities.